2007
DOI: 10.1007/s00418-007-0350-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in histochemistry

Abstract: The progress in discerning the structure and function of cells and tissues in health and disease has been achieved to a large extent by the continued development of new reagents for histochemistry, the improvement of existing techniques and new imaging techniques. This review will highlight some advancements made in these Welds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 258 publications
(220 reference statements)
0
1
0
Order By: Relevance
“…The cells are probably metaplastic Clara cells. In normal lungs, Clara cells are cuboidal non-ciliated secretory cells associated with lung homeostasis [24], but exposure to ovalbumin in mice provokes hypertrophy of the cells, which acquire a mucous cell phenotype [21]. Comparison of SNA and PAS staining showed that the same columnar epithelial cells reacted with both agents.…”
Section: Discussionmentioning
confidence: 99%
“…The cells are probably metaplastic Clara cells. In normal lungs, Clara cells are cuboidal non-ciliated secretory cells associated with lung homeostasis [24], but exposure to ovalbumin in mice provokes hypertrophy of the cells, which acquire a mucous cell phenotype [21]. Comparison of SNA and PAS staining showed that the same columnar epithelial cells reacted with both agents.…”
Section: Discussionmentioning
confidence: 99%